Exercise echocardiography as a screening test for coronary artery disease and correlation with coronary arteriography - Harbrecht, James J.; Vacek, James L.; Rosamond, Thomas L.; Kramer, Paul H. (1991)
We evaluated exercise echocardiography as a screening test for coronary artery disease in 228 patients, all of whom underwent subsequent coronary angiography. After an echocardiogram at rest was obtained, each patient performed maximal, symptom-limited, upright treadmill exercise, immediately after which repeat imaging was performed. The exercise echocardiogram was abnormal if any segment failed to become hypercontractile with exercise, and these regional wall motion abnormalities were used to predict the extent and distribution of coronary disease. At subsequent angiography, coronary stenosis was defined as significant if luminal diameter was reduced greater than or equal to 50%. Compared with electrocardiography, exercise echocardiography was more sensitive (97 vs 51%) and specific (64 vs 62%), and had higher positive (90 vs 82%) and negative (87 vs 28%) predictive accuracies. Exercise echocardiography was also highly predictive of the extent (no, 1-, 2- or 3-vessel disease) and distribution (which vessel) of coronary stenoses. It is concluded that exercise echocardiography is an excellent screening test for the presence, extent and distribution of coronary artery disease.